Tuesday
March 28, 2017

Post a New Question

Posted by on .

#21 -can you help me solve this equation:
3x^2 (2x - 2)

i keep getting: 6x ^2 -6



#22 can you check this one:
(2x ^2) (6x^2)
i got 12x



#23 can you check this one:
(4m^2 + m -2) + (-m^2 - 3m)
i got: -4m ^2 + 4m-2


#25 can you check this one:
(3x^2 -x -1) + (2x^2 + 2x -1)

i got: -6x ^2 +1x





#26 (-2n^3)(2n)

i am stuck i got: -2n^3 *2n

  • algebra - - ,

    for #26 i got: -4n^4

  • algebra - - ,

    #22 i got 12 x ^4

  • algebra - - ,

    #23 should be i got: 5m^2 - 2m -2

  • algebra - - ,

    # 21

    3 x ^ 2 ( 2 x - 2 ) =


    3 x ^ 2 * 2 x - 3 x ^ 2 * 2 =

    6 x ^ 3 - 6 x ^ 2 =

    6 x ^ 2 ( x - 1 )


    # 22

    ( 2 x ^ 2 ) ( 6 x ^ 2 ) =

    6 * 2 * x ^ 2 * x ^ 2 =

    12 x ^ 4


    # 23

    ( 4 m ^ 2 + m - 2 ) + ( - m ^ 2 - 3 m ) =

    4 m ^ 2 + m - 2 - m ^ 2 - 3 m =

    3 m ^ 2 - 2 m - 2


    # 25

    ( 3 x ^ 2 - x - 1 ) + ( 2 x ^ 2 + 2 x - 1 ) =

    3 x ^ 2 + 2 x ^ 2 - x + 2 x - 1 - 1 =

    5 x ^ 2 + x - 2


    # 26

    ( - 2 n ^ 3 )( 2 n ) =

    - 2 * 2 * n ^ 3 * n =

    - 4 n ^ 4

  • algebra - - ,

    bosnian
    for #23
    i got 5m ^2 - 2m - 2

    can you explain this one again

  • algebra - - ,

    ( 4 m ^ 2 + m - 2 ) + ( - m ^ 2 - 3 m ) =

    4 m ^ 2 + m - 2 + ( - m ^ 2 ) + ( - 3 m ) =

    4 m ^ 2 + m - 2 - m ^ 2 - 3 m =

    4 m ^ 2 - m ^ 2 + m - 3 m - 2 =

    3 m ^ 2 - 2 m - 2

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question